2 The ethics of (mis)representation of functional neurological disorders in public media. Issue 8 (13th July 2017) - Wardrope, Alistair; Reuber, Markus
Abstract : Objective: To describe two different cases of misrepresentations of functional neurological disorders in mass media (television) and review ethical issues faced by the health professional on viewing these. Method: Case series, narrative review and conceptual analysis Results: In the first case, a documentary shows emergency management of an individual in apparent status epilepticus who receives intensive invasive management. Follow-up in the documentary suggests the patient retains a diagnosis of epilepsy. However a viewing clinician believes the attack displayed to be non-epileptic in nature. The second case concerns the talk show appearance of a woman experiencing functional neurological symptoms including memory loss and weakness. During the course of the interview, several incorrect statements regarding the aetiology, management and prognosis of functional neurological disorders are made that may lead to inappropriately catastrophizing interpretations of the condition. A viewing clinician is concerned about the effect of these misleading statements on others who may experience similar symptoms. Such cases raise challenging questions regarding clinical workers' professional responsibilities in 'informal' contexts outside established professional-patient relationships, and their relationship with health journalists in mainstream media. The clinician must deliberate whether and how to engage with: the patients involved; the teams responsible for their care; the media outlets producing the content; and the viewing public. We find neither internalist approaches to professional responsibility (such as virtue ethics or care ethics), nor externalist ones (such as the 'social contract' model) are able adequately to engage with such situations – the former invoking norms grounded in pre-existing professional-patient relationships, the latter's guidance being too abstract. We explore these questions through an instrumentalised virtue ethics, emphasising the non-complacency and practical wisdom of virtue ethics, but grounding the normative authority of virtue in a physician's wider responsibility to serve public health. Conclusion: Health workers' caring responsibilities extend beyond established professional-patient relationships to informal encounters, but must be acted on in a way sensitive to the concrete particulars of the individual case, and to the limitations of the health worker's knowledge. Health workers can also promote better health through working toward public understanding of conditions in their field, and should engage with healthcare journalists to convey how specific vulnerabilities of patients experiencing conditions they are expert in lead to moral hazard.